PERAN ORIENTASI NILAI MANAJER PADA INOVASI DALAM MEMPENGARUHI HUBUNGAN ANTARA STRUKTUR DESENTRALISASI DAN PARTISIPASI ANGGARAN DENGAN KOMITMEN ORGANISASI PADA INDUSTRI PERBANKAN DI ACEH - Ika Rahmadani, Nadirsyah, Syukriy Abdullah. (Jurnal Akuntansi, 2016)
Abstract: The purpose of this study were to tests (1) the moderating role of managers’ value orientation towards innovation in the relationship between decentralised structure and organisational commitmen, (2) the moderating role of managers’ value orientation towards innovation in the relationship between budgetary participation and organisational commitment.The population of this study was 28 bank in Aceh Province. The data were then analyzed by using the quantitative analysis with the Moderated Regression Analysis technique. The results of the analysis indicate that (1) the moderating role of managers’ value orientation toward innovation is not able to strengthen the relationship between decentralised structure and their organizational commitment in such a way that the first hypothesis is not verified, (2) the moderating role of managers’ value orientation toward innovation is able to strengthen the relationship between budgetary participation and their organizational commitment in such a way that the second hypothesis is verified. Recomendation for the future research is to use other variable such as organisational culture or job satisfaction to see its colleration to organisational commitment.Keywords: decentralised structure, budgetary participation, organisational commitment, managers’ value orientation towards innovation.Abstrak:Penelitian ini bertujuan untuk menguji (1) peran orientasi nilai manajer pada inovasi dalam memperkuat hubungan antara struktur desentralisasi dengan komitmen organisasi, (2) peran orientasi nilai manajer pada inovasi dalam memperkuat hubungan antara partisipasi anggaran dengan komitmen organisasi. Populasi dalam penelitian ini adalah perbankan di Wilayah Aceh, dengan total sasaran sebanyak 28 bank. Metode analisis yang digunakan pada penelitian ini adalah Moderated Regression Analysis. Hasil penelitian menunjukkan (1) orientasi nilai manajer pada inovasi tidak mampu memperkuat hubungan antara struktur desentralisasi dengan komitmen organisasi, dan (2) orientasi nilai manajer pada inovasi mampu memperkuat hubungan antara partisipasi anggaran dengan komitmen organisasi. Pada penelitian selanjutnya peneliti merekomendasikan untuk memasukkan variabel lain seperti kepuasan kerja dan budaya organisasi untuk menilai komitmen organisasi.Kata Kunci: struktur desentralisasi, partisipasi anggaran, komitmen organisasi, orientasi nilai manajer pada inovasi.